Analisis Penerapan PSAK 109 (Revisi 2021) terhadap Penyajian Laporan Keuangan Lembaga Zakat di Baitulmaal Muamalat dan Implikasi Hukumnya - Intan Nur Apriliani; Panji Adam Agus Putra; Intan Manggala (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Amil zakat institutions must manage ZIS transparently and accountably according to sharia principles, as regulated in PSAK 109 (Revised 2021) concerning ZIS accounting. This PSAK functions as a guideline for recording financial report accounting, especially for zakat management organizations (OPZ). The purpose of this study was to determine the application of PSAK 109 (Revised 2021) in recording and reporting ZIS finances at the Baitulmaal Muamalat zakat institution and to determine law enforcement for zakat institutions that do not record ZIS fund management. This study uses a qualitative method with a sociological approach. Data were collected through observation, questionnaires, and documentation. The types of data used are primary data and secondary data. The data analysis technique was carried out descriptively through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study show 1) Baitulmaal Muamalat in preparing financial reports of zakat, infaq, and alms funds is not fully in accordance with PSAK 109 (Revised 2021). In terms of distributing zakat, infaq, and alms carried out through other entities, the implementation of Baitulmaal Muamalat in its accounting records must still comply with the provisions of PSAK 109 (Revised 2021). 2) Zakat institutions that do not record the management of ZIS funds in accordance with regulations may be subject to administrative sanctions such as written warnings, temporary suspension, and revocation of operational permits. These sanctions include ta'zir al-khashshah (sanctions of reduction of rights) given by BAZNAS or the Minister of Religion as the authorized authority. Abstrak. Lembaga amil zakat harus mengelola ZIS dengan transparan dan akuntabel sesuai prinsip syariah, seperti yang diatur dalam PSAK 109 (Revisi 2021) tentang akuntansi ZIS. PSAK tersebut berfungsi sebagai pedoman pencatatan akuntansi laporan keuangan terutama bagi organisasi pengelola zakat (OPZ). Tujuan penelitian ini untuk mengetahui penerapan PSAK 109 (Revisi 2021) pada pencatatan dan pelaporan keuangan ZIS di lembaga zakat Baitulmaal Muamalat dan mengetahui implikasi hukum bagi lembaga amil zakat yang tidak melakukan pencatatan pengelolaan dana ZIS. Penelitian ini menggunakan metode kualitatif dengan pendekatan sosiologi. Data dikumpulkan melalui observasi, angket, dan dokumentasi. Jenis data yang digunakan data primer dan data sekunder. Teknik analisis data dilakukan secara deskriptif melalui tiga tahapan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan 1) Baitulmaal Muamalat dalam menyusun laporan keuangan dana zakat, infak, dan sedekah belum sepenuhnya sesuai dengan PSAK 109 (Revisi 2021). Dalam aspek penyaluran zakat, infak, dan sedekah yang dilakukan melalui entitas lain, implementasi Baitulmaal Muamalat dalam pencatatan akuntansinya masih harus menyesuaikan dengan ketentuan PSAK 109 (Revisi 2021). 2) Lembaga zakat yang tidak mencatat pengelolaan dana ZIS sesuai regulasi dapat dikenai sanksi administratif seperti peringatan tertulis, penghentian sementara, dan pencabutan izin operasional. Sanksi ini termasuk ta’zir al-khashshah (sanksi pengurangan hak) yang diberikan oleh BAZNAS atau Menteri Agama sebagai otoritas yang berwenang.